The Role of Citizen Charter in Accelerating Public Service Delivery in Land Management: A Case Study Of Upazila Land Offices (Bangladesh Journal of Public Administration, 2022)
The proactive disclosure of relevant information is very important to get services since it is one of the powerful tools in terms of dominating others. Hence, in land management services, information is a very important element both for service providers and service recipients. Therefore, information can be used as a means of providing smooth service delivery and concealing proper information, the service recipients can also be pushed in immoral practices on the other hand. Considering the existing situation, the government is always trying to provide services to its citizens smoothly and easily through adopting and introducing different mechanisms and initiatives. The introduction of the citizen-charter in public offices is one of such initiatives. Consequence of which the present study investigated the contribution of citizen charter in accelerating public service delivery in land management in the country. It also explored the perception of service recipients about the citizen charter and factors affecting in implementation of the citizen charter. The study administered qualitative methodology and data have been collected from primary and secondary sources. The study revealed that citizen charter brings a positive impact on public service delivery in land management. Information about different services, their rate of fees and stipulated time-frame is displayed openly on the citizen charter notice board at the land office and also on its website. It has become easier due to the introduction of digitization in land administration. However, the study explored that the educational status of the service recipients is not an impending factor to get services from the land administration offices. Rather, the middleman or vested interest group is found as criminal-agent to make the as usual process of getting service difficult. It is happened due to the complex nature of the land management system and its complicated process of service delivery. Therefore, it is recommended to appoint more IT expert officials with an uninterrupted power supply and high-speed net connection at the ACLs offices for ensure accountability and effective monitoring systems along with more publicity about the citizen charter to create more awareness about it. Moreover, a huge campaign is needed to create awareness about the process of receiving services, fees, and levies for different services, sources of land-related information, etc. Initiatives should also be taken to develop professionalism and cooperative manners among ACL staff. Introduction of feedback—both service providers and service recipients—the system would be an effective mechanism, among many others, at the ACL offices in the country to provide better services and that can be a part citizen charter.